Kajian Potensi Sumber Mata Air Sungai Kamuyang, Kab. 50 kota Dengan Metode NRECA - Sari, Ridha; Asnur, Hanifah; Yunita, Rini (Jurnal Bangunan, Konstruksi & Desain, 2024)
50 Kota Regency has quite a lot of potential water sources. One of them is the Kamuyang River spring. This spring has been utilized by the surrounding community to meet their daily water needs. The abundant water discharge in the rainy season allows the utilization of this water to sometimes exceed the capacity that can be utilized by residents. However, it is possible that the discharge will decrease significantly in the dry season. This study examined how much potential the Kamuyang River spring can be utilized. The purpose of the study was to determine the amount of the mainstay discharge from the Kamuyang River spring using the NRECA method. The mainstay discharge taken was 80% reliability and 90% reliability of the discharge produced by the spring. From the calculation results, the mainstay discharge of 80% Q80 was obtained as 0.000424 m3/sec or equivalent to 36.599 m3/day, and the mainstay discharge of 90% Q90 was 0.000184 m3/sec or equivalent to 15.883 m3/day. By knowing the mainstay discharge from this water source, it is hoped that the utilization and exploitation of water at this location will not exceed the existing capacity so as not to damage the groundwater cycle in the Kamuyang River area and its surroundings.